Transcriptional Expression of Tissue Factor Pathway Inhibitor, Thrombomodulin and von Willebrand Factor in Normal Human Tissues - Bajaj, M. S.; Kuppuswamy, M. N.; Manepalli, A. N.; Bajaj, S. P. (Thrombosis and Haemostasis, 1999)
Under normal physiologic conditions, tissue factor pathway inhibitor (TFPI) is synthesized primarily by the microvascular endothelium. Using Northern blotting, we studied its transcriptional expression in different organs and compared it with the expression of two other endothelial specific proteins, namely thrombomodulin (TM) and von Willebrand factor (vWF). The order of mRNA expression for each protein was: TFPI–placenta>lung>liver>kidney>heart>skeletal muscle≥pancreas>brain; TM–heart>pancreas>lung>skeletal muscle>kidney≥liver>placenta>brain; and vWF–heart>skeletal muscle>pancreas>lung≥kidney>placenta>brain>liver. Notably, heart expressed TM and vWF mRNA in large amounts and only small amounts of TFPI whereas lung expressed all three mRNAs in significant amounts. Placenta, on the contrary, expressed large amounts of TFPI but only small amounts of TM and vWF mRNAs. Brain by this technique was found to express undetectable amounts of TFPI and TM mRNAs but small amounts of vWF mRNA. The expression of TFPI mRNA in the brain was however detected by RT/PCR and the antigen was localized to the endothelium of microvessels as well as to the astrocytes and oligodendrocytes. Since ultimate expression of proteins is linked to the expression of their mRNAs, our data support a concept that vascular endothelium is made up of phenotypically diverse groups of cells and that endothelial cells of different vascular beds express specific sets of genes that enable them to carry out tissue-specific functions. Importantly, since astrocytes are known to express tissue factor, the TFPI expression by these cells may control coagulation in their microenvironment and their response to injury and inflammation.